Nurses' Remaining in Everyday Nursing Practice-A Comprehensive Model - Margareth Kristoffersen PhD (SAGE Publishing, 2019)
Previous theoretical and empirical models of nurses' remaining in everyday nursing practice are explained by elements such as intent to stay and desire to stay. This study provides a model that expands or expresses an increased understanding of the comprehensiveness of the issue by pointing to the qualitative worth of different desires. The aim of this study is to describe a comprehensive model of nurses' remaining in everyday nursing practice. This study was designed in three sequential stages: first, the empirical foundation of the model; second, the development of the model; and third, the description of the model. The described model is derived from a previous qualitative study's comprehensive understanding of empirical findings. That original study was based on a hermeneutical approach, the aim of which was to understand what is of significance for nurses to remain in everyday practice. The collected data consisted of qualitative interviews and qualitative follow-up interviews with 13 nurses. The research context was the primary and secondary somatic and psychiatric health service. The present comprehensive model is stated in a simple structure, which nonetheless provides a relevant framework for constituent elements of nurses' remaining in everyday practice. Horizons of identity and self-understanding have been identified as constituent elements or key concepts involved in remaining. By focusing on a deepened and broader understanding, the model highlights that remaining may be constituted through a process of identification and taking standpoints, which in turn has a potential to empower nurses to realize themselves.